When red tape saves time: The Anti-corruption controls for the 2015 Universal Exposition - Simone Busetti; Bruno Dente (International Review of Public Policy)
When a major corruption scandal emerged during the organisation of the 2015 Universal Exposition in Milan, the government set up a brand-new system of preliminary controls for the procurement of all Expo contracts. Controls can certainly be beneficial in many respects, but they inevitably complicate procedures and even produce delays and red tape. Indeed, for a time-pressed schedule as that of the 2015 Expo, preliminary controls were considered a fatal blow. Contrary to expectations, not only bureaucratic delays did not materialise, but controls actually sped up procedures. Therefore, it is worth explaining and learning from this unique outcome. Can it be replicated in other cases? We answer this question by building a model of controls based on programme and non-programme features that support three causal mechanisms: threat attribution, repeated interactions, and actor certification. Such a model is an indispensable tool for designers; it allows to explain how controls work in practice and provide clues on how to adjust the design of the policy to changing contexts. In this respect, the analysis of the Expo controls and their subsequent replications raises several methodological issues relevant to extrapolation-oriented research.